General properties of interaction currents of higher spin fermions and their consequences for πN–scattering - Kulish, Yu.V.; Rybachuk, E.V. (Вопросы атомной науки и техники, 2012)
The model for the currents of interactions of higher spin fermions with the 0- and 1/2-spin particles is proposed. These currents obey to the theorem on currents and fields as well as the theorems on current asymptotics. The comparison of the proposed model with partial wave analysis of the πN–scattering in Δ(1232)-region shows the validity of the theorem on currents and fields. It is shown that in consequence of the theorems on current asymptotics the contributions of higher spin nucleon resonances to πN–scattering amplitudes must decrease at high energy at least as s⁻⁶.